Desempenho de bezerras e bezerros lactentes da raça Jersey em diferentes abrigos - Bidin, Bruna (2019)
The objective of this study was to evaluate the performance of calves and heifers from birth to 60 days of age, with the same amount and quality of diet during this period in two different types of shelters. This experiment was carried out during the winter / spring period of 2018 (June to November), at the UNEPE of Dairy Cattle of the Universidade Tecnológica Federal do Paraná (UTFPR) - Campus Dois Vizinhos. Six animals (heifers and calves) Jersey were used with an experimental design in randomized blocks according to the order of birth, in both treatments.,The treatment 1 were individual bays with concrete floor and treatment 2 the Argentinean individual shelter. Physiological variables such as respiratory rate (RF), heart rate (HR) and rectal temperature (RT) were evaluated. Morphometric variables such as height at withers (CA), croup height (GA) and chest circumference (CT) were evaluated using the tape measure. Periodicity of 15 days between one measurement and another. Other measurements, such as initial weight, final weight and daily weight gain were also analyzed. The incidence of diarrhea was also observed, where treatment 1 had 100% of the affected animals, while in treatment 2 the percentage of the affected animals was 66.66%, having a calf not affected by this disease. None of the results differed significantly according to Tukey's test with 5% significance.